1998
DOI: 10.1006/viro.1998.9039
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Sequence Analysis of the Left and Right Species-Specific Terminal Region of a Cowpox Virus Strain Reveals Unique Sequences and a Cluster of Intact ORFs for Immunomodulatory and Host Range Proteins

Abstract: Sequencing and computer analysis of the left (52,283 bp) and right (49,649 bp) variable DNA regions of the cowpox virus strain GRI-90 (CPV-GRI) has revealed 51 and 37 potential open reading frames (ORFs), respectively. Comparison of the structure-function organization of these DNA regions of CPV-GRI with those previously published for corresponding regions of genomes of vaccinia virus, strains Copenhagen (VAC-COP) and Western Reserve (VAC-WR); and variola major virus, strains India-1967 (VAR-IND), Bangladesh-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
145
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 109 publications
3
145
0
3
Order By: Relevance
“…and others 1998). On the other hand, CPV GRI-90 has four different TNFR-like genes (Shchelkunov et al, 1998), three of which express a vTNFR (Hu et al, 1994 ;Smith et al, 1996 ;Loparev et al, 1998). A soluble vTNFR has been predicted from sequence similarity in lymphocystis disease virus (Tidona & Darai, 1997), a large DNA iridovirus that infects fish, consistent with the conservation of TNF throughout evolution (Beck & Habicht, 1991).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…and others 1998). On the other hand, CPV GRI-90 has four different TNFR-like genes (Shchelkunov et al, 1998), three of which express a vTNFR (Hu et al, 1994 ;Smith et al, 1996 ;Loparev et al, 1998). A soluble vTNFR has been predicted from sequence similarity in lymphocystis disease virus (Tidona & Darai, 1997), a large DNA iridovirus that infects fish, consistent with the conservation of TNF throughout evolution (Beck & Habicht, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the ability of CrmD and the putative VV vTNFR to bind LTα differ, and our studies found no cell-surface vTNFR expressed by this strain of CPV. Another possibility is that the fourth ORF with sequence similarity to TNFR superfamily members that was identified in CPV strain GRI-90 (K3R) (Shchelkunov et al, 1998) represents the novel VV vTNFR, although no TNFR activity has been demonstrated for K3R. However, neither CrmD nor K3R were reported to have membrane-anchoring domains (Loparev et al, 1998 ;Shchelkunov et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic comparisons suggest that CPV is an ancestor of other orthopoxviruses (3), including VAR, which is now considered a bioterrorist threat. This ancestral role of CPV is supported by the observation that CPV contains the most complete set of immune modulators, of which many are mutated and/or deleted in vaccinia virus (VV) (4). It is likely that these mutations and deletions contribute to its diminished virulence and success as an attenuated vaccine against smallpox (5) CPV is thus an excellent model for identifying immune modulators of orthopoxviruses and their relationship to viral virulence.…”
mentioning
confidence: 99%
“…CPV is a good model to study the viral modulation of the inflammatory response because it encodes several proteins that can influence the inflammatory response, e.g., the complement control protein termed inflammation modulatory protein (IMP), the interleukin-1 (IL-1) receptor-like protein termed CrmB, the IL-1␤-converting enzyme inhibitor (ICE/Caspase), termed CrmA, the tumor necrosis factor (TNF) receptor-like protein CrmC, and the macrophage inflammatory protein-1␣ (MIP-1␣) receptor-like protein. Our studies have also shown that of all the orthopoxviruses (a group that includes vaccinia and variola viruses), CPV seems to be the most ancient and has the most complete and intact repertoire of open reading frames (ORFs) for immunomodulatory proteins [2]. Because rodents are the primary reservoir hosts for cowpox virus, a number of different knockout mice can be employed to characterize the contribution and relative importance of an individual host defense molecule in response to viral infection as well as to evaluate the role of an individual viral protein in its interaction with the immune system.…”
Section: Introductionmentioning
confidence: 82%